The innovation society and intellectual property - Drexl, Josef, 1962-; Kamperman Sanders, Anselm, 1968- (European intellectual property institutes network, 2019)
"Intellectual property (IP) rights impact innovation in diverse ways. This book critically analyses whether additional rights beyond patents, trademarks and copyrights are needed to promote innovation. Featuring contributions from thought-leaders in the field of IP, this book examines the check and balances that already exist in the IP system to safeguard innovation and questions to what extent existing IP regimes are capable of catering to new paradigms of innovation and creativity. Taking a multi-angled view of the topic, this book questions whether IP rights by definition encourage innovation and explores the role of exceptions and limitations to IP rights as well as the application of competition law to promote innovation. Chapters analyse diverse topics within the field of IP such as plant varieties protection, geographical indications and 3D printing. Taken as a whole this book advocates that a pro-innovation rationale must be applied when new IP legislation is designed. This book will be an engaging source of information for researchers and policy-makers with an interest in the direction of IP legislation and the promotion of innovation. It will also be relevant for scholars of competition law who are seeking information on the relationship between competition and IP"--